Structural dataset from microsecond-long simulations of yeast mitofusin Fzo1 in the context of membrane docking - Brandner Giménez, Astrid; De Vecchis, Dario; Baaden, Marc; Cohen, Mickael M; Taly, Antoine (Data in Brief, 2019)
In this work we present a novel set of possible auto-oligomerisation states of yeast protein Fzo1 in the context of membrane docking. The dataset reports atomistic models and trajectories derived from a molecular dynamics study of the yeast mitofusin Fzo1, residues 101–855. The initial modelling was followed by coarse-grained molecular dynamics simulation to evaluate the stability and the dynamics of each structural model in a solvated membrane environment. Simulations were run for 1 μs and collected with GROMACS v5.0.4 using the martini v2.1 force field. For each structural model, the dataset comprises the production phase under semi-isotropic condition at 1 bar, 310 K and 150 mn NaCl. The integration step is 20 fs and coordinates have been saved every 1 ns. Each trajectory is associated with a ready-available visualization state for the VMD software. These structural detailed informations are a ready-available platform to plan integrative studies on the mitofusin Fzo1 and will aid the community to further elucidate the mitochondrial tethering process during membrane fusion. This dataset is based on the publication “Physics-based oligomeric models of the yeast mitofusin Fzo1 at the molecular scale in the context of membrane docking.” (Brandner and De Vecchis et al., 2019)”.
Keywords: Fzo1; Mitochondrial fusion; Mitofusin; Modelling; Molecular dynamics; Structure; Tethering